MODELING PROCESSES A DUAL-LAYER IRON REMOVAL FILTERS - , Я. А., О. О. (Municipal economy of cities. Series: «Economy science», 2013)
A theoretical justification and proposed analytical expressions for calculating treatment filters with two-layer load for iron removal. The mathematical models of processes and proposals for their refinement with filtering double-layer filters.